Perjuangan Haji Agus Salim bagi Kemerdekaan Indonesia - Muria, Muria; Bahadin, Muhammad Irvan (Syams, 2023)
This study investigates the role and contribution of an Indonesian nationalist anddiplomat named Haji Agus Salim in the Indonesian independence movement in the 20thcentury. In this abstract, their background, activities and influence in Indonesia's struggle togain independence from colonialism are discussed. Intellectual, politician and diplomat HajiAgus Salim was active in the Indonesian national movement. He was born in Kota Agung,South Sumatra, on October 8 1884. He studied in Mecca, Egypt and the Netherlands.Haji Agus Salim supported Indonesian independence through many political and diplomaticactivities.